Autoignition of isolated n-heptane droplets in air and hot combustion products at microturbine conditions - Wang, Jiayi; Mastorakos, Epaminondas (Combustion theory and modelling, 2022)
Spontaneous ignition of isolated n-heptane droplets with initial diameters of 20-100 is simulated using air at 4 atm and 700-1200 K, which includes the typical operating conditions of recuperated microturbines. Because some fuel droplets in a combustor may be sprayed or carried to near the recirculation zone, the simulations use a mixture of pure air and hot combustion products as the oxidiser. The flame structures, evaporation times, and autoignition times in both physical and mixture fraction spaces for the different conditions are presented and compared. The variables examined include the air preheat temperature, amount of dilution with hot products, initial fuel droplet diameter, oxidiser temperature, and oxygen concentration. The results show that droplets in pure air at microturbine conditions fully evaporate before ignition, suggesting that a prevaporised concept is suitable for microturbines. The dilution with hot combustion products decreases the ignition delay time mainly by raising the oxidiser temperature. Low-temperature chemistry does not have a significant effect on droplet ignition because adding even a small amount of hot combustion products can increase the oxidiser temperature to higher than the temperatures favourable for low-temperature kinetics. The cool flame is only observed for 100 droplets at low temperatures, but two-stage ignition is not observed.